Сталий розвиток – панацея чи утопія? - Чуйков, Д. В. (ХНУРЕ, 2024)
This work is devoted to the issues of sustainable development and the goals set by the UN until 2030. The basics of the concept of sustainable development of the world are considered. The position of the leadership of Ukraine on this concept and state documents regulating issues of the Sustainable Development Goals in our country are being studied. Questions related to the criticism of the concept of sustainable development and the attitude towards it as a utopia are raised.
Keywords: антропогенний вплив; сталий розвиток